Analysis of Attack Types on TCP/IP Based Networks via Exploiting Protocols - Karadogan, Ismail; Das, Resul (Ieee, 2015)
The packets of the communication protocols contain header information and the actual data (payload) to be transmitted. In this study, types of attacks carried out by changing the header information that is used to transmit payload, or exploiting such processes as connection establishing or termination in TCP/IP network will be discuss.
TCP/IP Tabanli A?larda Protokollerin Istismariyla Yapilan Saldiri Türlerinin Analizi
23nd Signal Processing and Communications Applications Conference (SIU) -- MAY 16-19, 2015 -- Inonu Univ, Malatya, TURKEY
Keywords: TCP/IP; protocols; information security; network attacks